The Positivity of Contradiction. Some Remarks on Hegel’s and Fichte’s Philosophical Method (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: Fichte and Hegel elaborate a comparable account of contradiction that has to be distinguished from the Aristotelian tradition. Other than in traditional philosophy, contradictions are not in every case conceived as an indicator for erroneous reasoning. Moreover, contradicting assertions are essential to their philosophical method. In his Grundlage der gesamten Wissenschaftslehre, Fichte discusses the relation between absolute and finite subjectivity. In this context, his theory of synthesis and contradiction is worked out roughly. The unavoidable contradiction between the I and Not-I has to be resolved by introducing the term ‘quantity’. In the Wissenschaft der Logik, Hegel gives a more detailed, but closely related account of contradiction. He demonstrates that oppositions as such contradict, because the opponents, the positive and the negative, are contradictory in themselves and have to be resolved into the ground. Thereby, contradictions become productive.